On Location in Cuba : Street Filmmaking during Times of Transition - Stock, Ann Marie (Book collections on Project MUSE., 2009)
The 1990s were a time of dramatic transformation for Cuba. With the collapse of its Cold War relationship with the Soviet Union, the island nation plummeted into an era of scarcity and uncertainty known as the Special Period, a time from which it emerged only slowly in the new century. On Location in Cuba views these pivotal decades through the lens of cinema. Ann Marie Stock conducted hundreds of interviews and conversations in Cuba to examine individual artists' lives and creative output--including film, video, and audiovisual art. She explores the impact of the Cold War's end, the economic c.